Extracción, purificación y transformación enzimática del ácido clorogénico da la pulpa de café - Rodríguez Durán, Luis Víctor (Universidad Autónoma Metropolitana, 2016)
Coffee pulp (CP) is the main solid by-product obtained from wet processing of coffee cherries and it represents about 40% of fresh weight of coffee fruits. Annual production of CP in Mexico is over 400 000 tonnes, and traditional applications only use a fraction of this by-product. Thus, it is necessary to find alternative uses for CP. One of the most promising applications for valorization of CP consists of obtaining valuable natural compounds with biological activities. In the present study, we developed methodologies for the extraction and purification of chlorgenic acid (CGA) from CP. The CGA obtained was used as substrate for the enzymatic synthesis of caffeic acid phenethyl ester (CAPE). As a first step, we analyzed the content of soluble and insoluble hydroxycinnamic acids (HCAs) in CP obtained from fruits of seven cultivars at three ripening stages, as well as CP from a commercial process. HCAs were mainly in the soluble fraction (68-97%) of CP. CGA was the most abundant phenolic acid in this fraction (94-98%). While caffeic acid (CA) was the most abundant phenolic acid in the insoluble fraction (72-88%). Total HCAs content in CP increased from unripe stage (2.0-10.7 mg/g CP) to the semi-ripe stage (7.4-25.5 mg/g CP), but decreased at the ripe stage (3.0-6.5 mg/g CP) for six of the seven analyzed cultivars. The highest content of total HCAs (25.2-25.5 mg/g CP) was found in CP obtained from semi-ripe fruits from Yellow and Red Garnica cultivars. However, CP from a commercial was selected for preparative extraction of CGA because of their greater availability. In a second stage, a new methodology for the rapid extraction and purification of CGA from CP was developed. Final procedure consisted of microwave assisted extraction (MAE) followed by column chromatography on Amberlite XAD-16 and semi-preparative HPLC using a C18 column. It was possible to extract 71.6% of total CGA from CP by MAE in a short extraction time (4 min). The proposed MAE is a simple and reproducible process, not requiring the use of toxic solvents. The methodology used for the purification led to obtaining a CGA rich extract with a purity of 61.7% and a yield of 43.4% in a quick and simple process. Later, ten fungal strains were evaluated for their ability to grow on agar plates with CGA as sole carbon source, to form hydrolysis halos and to produce chlorogenate hydrolase activity in a solid state fermentation (SSF) system. All tasted strains were able to grow in this medium, but only strains from the genus Aspergillus produced halos of hydrolysis and chlorogenate hydrolase activity. Differences between chlorogenate hydrolase activity production profiles, maximum activity and productivity were found. However, these differences were not decisive for selecting a microorganism to produce chlorogenate hydrolase activity. Therefore, the enzymatic extracts produced by nine Aspergillus strains were tested as catalysts for enzymatic synthesis of CAPE from CA, CGA and CGA-rich extracts obtained from CP was studied. In the last stage, enzymatic synthesis of CAPE catalyzed by commercial enzymes and crude extracts produced by fungi in SSF was studied. Immobilized lipase B from C. antarctica (Novozyme® 435) catalyzed the synthesis of CAPE by esterification between CA and 2-phenylethanol (2-PE), but not by transesterification between CGA and 2-PE (yield < 1%). The esterification between CA and 2-PE and the transesterification between CGA and 2-PE in water-AOT-isooctane microemulsions was catalyzed by NS22002 hemicellulase at a much higher rate than the same reactions catalyzed by a C. antarctica lipase B CALB (kinetic constant k 8 and 990 times higher for esterification and transesterification reactions, respectively). Enzymatic synthesis of CAPE catalyzed by NS22002 lipase and enzymatic extracts produced in SSF is possible using analytical grade CGA as well as CGA-rich extracts obtained from CP. The yields obtained using a concentrated enzymatic extract from A japonicus AN5 (34.48-37.10%) were lower than those obtained with NS22002 (47.31- 53.57%), but higher than those reported for a chlorogenate hydrolase from A. ochraceus (9.4%). During enzymatic synthesis of CAPE from CGA in microemulsions, GCA hydrolysis and CA formation was observed. In the system catalyzed by NS22002 hemicellulase, accumulation of CA and CAPE occurred simultaneously (parallel reactions). Whereas in the system catalyzed by enzymatic extracts from Aspergillus spp., accumulation of CA and CAPE occurred sequentially (consecutive reactions). A pseudo first order kinetic model successfully modeled CGA, CA and CAPE concentrations in both systems. The results obtained in this study show that it is possible to extract, purify and transform CGA from CP to obtain valuable compounds as CAPE. The proposed methodology can be used to give added value to an agro-industrial by-product currently underutilized in our country. However, it requires further research to optimize these processes and make them economically more attractive.; La pulpa de café (PC) es el principal subproducto sólido derivado del beneficio húmedo del café y representa alrededor del 40% del peso fresco del fruto. Anualmente se producen más de 400 000 toneladas de PC en México y las aplicaciones tradicionales sólo aprovechan una fracción de este subproducto. Por ello, es necesario encontrar usos alternativos para la PC. Una de las aplicaciones más prometedoras para valorizar este subproducto consiste en la obtención de valiosos compuestos naturales con actividades biológicas. En el presente trabajo se desarrollaron metodologías para la extracción y purificación del ácido clorogénico (ACL) de la PC, el cual se utilizó para la síntesis enzimática de éster fenetílico del ácido cafeico (CAPE). En la primera etapa experimental, se analizó el contenido de ácidos hidroxicinámicos (AHCs) solubles e insolubles de la PC obtenida de frutos de siete variedades en tres diferentes estados de madurez, así como muestras de PC provenientes de un beneficio comercial. Todos los frutos fueron cultivados en el Estado de Veracruz. Los AHCs se encontraron principalmente en la fracción soluble en metanol (68-97%) de la PC. El ACL fue el ácido fenólico más abundante en la fracción soluble (94-98%), mientras que el ácido cafeico (AC) fue el ácido fenólico más abundante en la fracción insoluble (72-88%). El contenido total de AHCs de la PC se incrementó del estado inmaduro (2.0-10.7 mg/g PC) al estado semi-maduro (7.4-25.5 mg/g PC) pero disminuyó en el estado maduro (3.0-6.5 mg/g PC) para seis de las siete variedades analizadas. El mayor contenido de AHCs (25.2-25.5 mg/g PC) se encontró en la PC obtenida de los frutos semi-maduros de las variedades Garnica Rojo y Garnica Amarillo. Sin embargo, se seleccionó la PC obtenida del proceso comercial para la extracción preparativa de ACL debido a su mayor disponibilidad. En una segunda etapa se desarrolló una metodología para la extracción y purificación rápida del ACL de la PC. El protocolo final consistió en una extracción asistida por microondas (EAM) seguida de una cromatografía en una columna empacada con amberlita XAD-16 y una cromatografía en HPLC semi-preparativo usando una columna C18. Con la EAM se recuperó el 71.6% del ACL total de la PC en un corto tiempo de extracción (4 min) mediante un proceso rápido, sencillo y reproducible. La metodología propuesta para la purificación del ACL permitió la obtención un extracto con una pureza del 61.7% con un rendimiento del 43.4% en un proceso rápido. Posteriormente se evaluaron 10 cepas fúngicas por su capacidad para crecer en placas de agar con ACL como única fuente de carbono, formar halos de hidrólisis de ACL y producir enzimas con actividad clorogenato hidrolasa en un sistema de fermentación en medio sólido (FMS). De las 10 cepas evaluadas, las del género Aspergillus produjeron halos de hidrólisis y actividad clorogenato hidrolasa. Se encontraron diferencias entre los perfiles de producción de actividad clorogenato hidrolasa, actividad máxima y productividad obtenidas con diferentes microorganismos. Sin embargo, estas diferencias no fueron determinantes para seleccionar una cepa para la producción de actividad clorogenato hidrolasa. Por ello, los extractos producidos por las nueve cepas del género Aspergillus se probaron como catalizadores para la síntesis enzimática de CAPE a partir de AC, ACL y extractos ricos en ACL obtenidos de la PC. En la última etapa se estudió la síntesis enzimática de CAPE catalizada por enzimas comerciales y extractos enzimáticos producidos por FMS. La lipasa B de C. antarctica inmovilizada (Novozym® 435) es capaz de catalizar la síntesis de CAPE por esterificación entre AC y alcohol fenetílico (2-FE), pero no por transesterificación entre ACL y 2-FE (rendimiento < 1%) usando isooctano como medio de reacción. El uso de disolventes y cosolventes más polares mejoró la solubilidad del AC, pero no incrementó el rendimiento de la reacción. Las reacciones de esterificación entre AC y 2-FE y de transesterificación entre ACL y 2-FE en microemulsiones (agua-AOT-isooctano) catalizadas por lhemicelulasa NS22002 fueron mucho más rápidas que las mismas reacciones catalizadas por una lipasa B de C. antarctica (CALB) (constante cinética, k, 8 y 990 veces mayor, para las reacciones de esterificación y transesterificación, respectivamente). La síntesis enzimática de CAPE catalizada por NS22002 y por extractos enzimáticos producidos en FMS fue posible usando ACL grado analítico, así como extractos ricos en ACL obtenidos de la PC. Los rendimientos obtenidos usando un extracto enzimático concentrado de A japonicus AN5 (34.48-37.10%) fueron menores a los obtenidos con la enzima comercial NS22002 (47.31-53.57%), pero mayores a los reportados en la bibliografía para una clorogenato hidrolasa de A. ochraceus (9.4%). Durante la síntesis enzimática de CAPE a partir de ACL en microemulsiones se observó la formación de AC por hidrólisis del ACL. En el sistema catalizado por la hemicelulasa NS22002, la acumulación de AC y CAPE ocurrió de manera simultánea (reacciones en paralelo). Mientras que en el sistema catalizado por los extractos enzimáticos de Aspergillus spp., la acumulación de AC y CAPE se dio de manera secuencial (reacciones en serie). La concentración de ACL, AC y CAPE en ambos sistemas fue modelada satisfactoriamente con un modelo cinético de pseudo primer orden. Los resultados obtenidos en el presente trabajo demuestran que es posible extraer, purificar y transformar el ACL de la PC para obtener compuestos valiosos como el CAPE. La metodología desarrollada puede utilizarse para dar un valor agregado a un subproducto agroindustrial actualmente subutilizado en nuestro país. Sin embargo, se requiere de mayor investigación para optimizar estos procesos y hacerlos económicamente más atractivos.